Good practices for reporting the photocatalytic evaluation of a visible-light active semiconductor: Bi2O3, a case study. Issue 6 (4th March 2019) - Hernández-Gordillo, Agileo; Bizarro, Monserrat; Gadhi, Tanveer A.; Martínez, Ana; Tagliaferro, Alberto; Rodil, Sandra E.
Abstract : The use of dyes to evaluate visible-light photocatalysts requires a proper determination of the contribution from the competing processes: adsorption, sensitization, photobleaching and degradation. Abstract : In this paper, we discuss the importance of distinguishing the contributions of photolysis, adsorption, sensitization, degradation and mineralization processes to the photocatalytic activity of a visible-light active semiconductor: Bi2 O3 . Based on this case study, we propose a follow-up work plan to obtain the relevant information and achieve proper interpretation of reported data to adequately infer the photocatalytic activity of the Bi2 O3 material. To do so, we compared the changes in the theoretical and experimental absorbance spectra of three different dyes during the photodegradation process: rhodamine-B (RhB), acid blue 113 (AB) and indigo carmine (IC). Photocatalytic degradation of these dyes using the same semiconductor material (Bi2 O3 ) was performed using the standard spectrocolorimetric method while taking care to appropriately consider the competing processes mentioned above. Furthermore, the degree of mineralization achieved due to the photocatalytic degradation of the dyes was obtained using the total organic carbon (TOC) analysis. The commonly used evaluation of the results suggests that a certain degree of photodegradation and mineralization was achieved. However, careful analysis indicates that this was mainly due to a decrease in the relative concentration of the dye molecules in the solution because of their adsorption on the surface of the semiconductor and not to complete degradation.